The relationship between marital satisfaction with demographics characteristics in the population of Tehran 2016 - Taban, Mozhgan; Dolatshahi, Behrooz; Eftekhar, Mehrdad; Pourshabaz, Abbas (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: The family has important and multiple effects on various aspects of individual and social life. Marital satisfaction influences on the family. The aim of current study was to determine the effects of demographic factors on marital satisfaction in selected population of Tehran. Materials and Methods: This was a descriptive cross-sectional study. The sample was of 90 couples (180 individuals) which were selected by convenience sampling from the people who were working in centers affiliated to the Ministry of Health. They had spent at least two years of marriage, and they didn’t have addiction and severe psychiatric disorders. After removing the falsified questionnaires, the 80 couples (160 individuals) were investigated. Enrich marital satisfaction questionnaire and a researcher- made demographic characteristics questionnaire were completed for each couple. Data were analyzed by Pearson’s correlation and paired t-test. Results: The relationships between age (p=0.07 for women & p=0.85 for men), family size (p=0.07 for women & p=0.8 for men), income (p=0.09 for women & p=0.6 for men), difference age of couple (p=0.92 for women & p=0.55 for men) and length of marriage (p=0.36 for women & p=0.36 for men) and marital satisfaction were not significant. Conclusion: Marital satisfaction scores were higher than expected in women and men. Also no significant relationship with determinant variables was not consistent with some studies. This issue shows need further examination to generalize the results to other couples. Keywords: Satisfaction, Marital Relationship, Demographic Factors